Using arts-based research to help visualize community intervention in international aid. (September 2015) - Huss, Ephrat; Kaufman, Roni; Avgar, Amos; Shouker, Eytan
This article discusses the advantages of arts-based research specifically for high-context, culturally diverse, power-infused, and chaotic or diffuse research settings as often found in international aid. It points to the ability of arts to concretize abstract concepts and to situate them within specific socio-cultural locations, enabling powerless groups to self-define and to adjust resilience-enhancing interventions to their own perceptions. The arts-based method as an indirect form of communication is shown to be effective in changing stands of power holders and experts, enabling a dialogue that creates culturally sustainable aid. The model used in this article is demonstrated and discussed.